From Developers to Players: Exploring the Dual Impact of Game-Based Learning on Student Engagement, Learning and Skill Development - CANAVESI, Alice; BERTOLOTTI, Francesco; CATTANEO, Laura; BUONANNO, Giacomo; MARI, Luca; RAVARINI, Aurelio (Journal of Research in Educational Sciences; Vol 16 No 2 (2025): JRES, Volume XVI, Issue 2(20), Winter 2025DO - 10.14505/jres.v16.2(20).01, 2025)
This paper explores the implementation of Game-Based Learning (GBL) in higher education, with a particular focus on the dual role of students as developers and players of educational games. In particular, the study investigates the extent to which GBL leverages intrinsic motivation, fosters engagement, consolidates prior knowledge, and cultivates essential 21st-century skills in undergraduate students that designed, developed, and played interactive digital gamebooks on STEM disciplines. A mixed method based on surveys and focus groups was leveraged to assess the diverse learning outcomes and the educational impact of the project. Findings highlights that the GBL approach significantly increased student engagement, fostered deeper learning in IT-related skills, and provided valuable experiences in competences such as project management and teamwork. However, the integration of advanced academic content in Mathematics and Statistics was perceived as less effective, posing challenges to knowledge acquisition and consolidation. This study shows that while GBL is highly effective in promoting motivation and skill development, further refinement is needed to align content complexity with learning objectives.